The Selection and the Growth Condition Optimization of Ethanolâ€Producing Microbes Isolated from Ragi Tapai: Selection and the Growth Condition Optimization of Ethanolâ€Producing Microbes - Ida Bagus Wayan Gunam; I Gede Arya Sujana; I Made Mahaputra Wijaya; Yohanes Setiyo; I Wayan Arnata; I Wayan Wisma Pradnyana Putra (Journal of Tropical Life Science, 2023)
Ethanol is a biofuel produced from renewable resources, which potentially plays an important role in solving future fuel problems. This study aimed to select the highest ethanol-producing isolate from candidates obtained from previously isolated candidates from ragi and cassava tapai. The selection process was conducted in 2 stages, namely: 1) Selection of the highest ethanol-producing isolate from seven isolate candidates using PYG media containing peptone, yeast extract, and glucose at 0.75%, 0.75%, and 15%, respectively and was followed by: 2) Optimization of the growth conditions of the highest ethanol-producing isolate, which was conducted at various temperatures of 27, 30, 33, 35, 37, and 40°C with the combination of various pH of 3.5, 4.5, 5.5, and 6.5. The experimental results showed that the R5I3 isolate was the highest ethanol-producing performance isolate, which yielded approximately 4.69±0.25% (v/v). Following the temperature and pH optimization of the fermentation processes, the optimum growth conditions were at 35°C and pH 5.5, where the ethanol produced was increased to 8.63 ± 0.04% (v/v). With these results, this new strain has the potential to be used in bioethanol production processes and other industrial applications.